2015
DOI: 10.1007/s11097-014-9408-5
|View full text |Cite
|
Sign up to set email alerts
|

From clumsy failure to skillful fluency: a phenomenological analysis of and Eastern solution to sport’s choking effect

Abstract: Excellent performance in sport involves specialized and refined skills within very narrow applications. Choking throws a wrench in the works of finely tuned performances. Functionally, and reduced to its simplest expression, choking is severe underperformance when engaging already mastered skills. Choking is a complex phenomenon with many intersecting facets: its dysfunctions result from the multifaceted interaction of cognitive and psychological processes, neurophysiological mechanisms, and phenomenological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…If this is so, then positive , as well as non-judging and hence anxiety-free, forms of self-evaluation should give no reason to try to bring thoughts, emotions (or maybe even the movements themselves) under control and hence not interfere with automatic movement processes. This has already been noticed in Wulf and Lewthwaite (2010): “It may be that active self-regulatory activities do not ensue, or at least demand less effort and attention, when positive self-regard and optimal task performance are experienced.” As Ilundain-Agurruza (2015) pointed out, important is not only what one attends to but also how one does so. Viewed in this light, it is not at all clear how different the view expressed in Toner and Moran (2015) really is from the prevailing view about the optimality of an external focus of attention: “careful attention to our bodily means (and attendant feelings) of action” could very well be read as paying attention to the quality of what one is doing, hence an external focus.…”
Section: Focus Of Attention and “Awareness Through Movement”mentioning
confidence: 99%
See 2 more Smart Citations
“…If this is so, then positive , as well as non-judging and hence anxiety-free, forms of self-evaluation should give no reason to try to bring thoughts, emotions (or maybe even the movements themselves) under control and hence not interfere with automatic movement processes. This has already been noticed in Wulf and Lewthwaite (2010): “It may be that active self-regulatory activities do not ensue, or at least demand less effort and attention, when positive self-regard and optimal task performance are experienced.” As Ilundain-Agurruza (2015) pointed out, important is not only what one attends to but also how one does so. Viewed in this light, it is not at all clear how different the view expressed in Toner and Moran (2015) really is from the prevailing view about the optimality of an external focus of attention: “careful attention to our bodily means (and attendant feelings) of action” could very well be read as paying attention to the quality of what one is doing, hence an external focus.…”
Section: Focus Of Attention and “Awareness Through Movement”mentioning
confidence: 99%
“…Connected with choking under pressure, Ilundain-Agurruza (2015) discussed traditional Japanese swordsmanship as a case study of extreme pressure to perform, and in particular the idea of mushin : the concept of an imperturbable mind (literally, “no mind”) that is able to uphold fluid attention unperturbed by thoughts and emotions. Practice forms like Iaido (the art of drawing the sword) are movement meditation techniques that help attain mushin through mindfulness in that “[t]hose trained in these ways are mindfully aware without remaining fixed.” A modern Japanese martial art with deep roots in ancient swordsmanship is Aikido; for this art, which Lothes, Hakan, and Kassab (2013) called a form of “meditation-in-action,” these authors provided some evidence that its practice increases mindfulness.…”
Section: Mindful Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wiersma (2014) completed phenomenological interviews with elite big-wave surfers and found that they navigated their focus of attention to ensure that they were simultaneously aware of what was happening in front of (e.g., the contours and bumps of the water), and behind (e.g., the sound of what the wave was doing), their board so that they react accordingly. The type of awareness required in such situations would not involve the computationally demanding process of analyzing each step-by-step component of the desired action but instead requires the performer to attend to certain cues, or kinesthetic sensations (see Ilundáin-Agurruza, 2015, for a similar argument relating to the role of “kinesthetic attunement”) during online movement control. Indeed, an elite trampolinist in Hauw and Durand's (2007) study sought to avoid injury (as a result of poor execution) by using kinesthetic feedback to survey body position and the tautness and flexibility of the trampoline bed.…”
Section: Errors That Results From Slips In the Course Of Executionmentioning
confidence: 99%
“…Achieving success in sport is the result of many physical and psychological factors, but arguably one of the most important psychological factors is having the ability to perform optimally in high-pressure situations (Geukes, Mesagno, Hanrahan, & Kellmann, 2013;Ilundáin-Agurruza, 2015;Mesagno & Hill, 2013). For some athletes, however, the ability to perform successfully under pressure remains elusive, where choking under pressure (i.e., choking) may occur.…”
mentioning
confidence: 99%